UNMET MEDICAL NEED – CLINICAL ASPECT - Veličković Radovanović, Radmila (Archives of Pharmacy, 2023)
An unmet medical need (UMN) is a condition or symptom whose treatment or diagnosis is not addressed adequately by available therapy. An UMN includes an immediate need for a defined population or a longer-term need for society (e.g., to address the development of resistance to antibacterial drugs)(1). It plays an important role in investment and priority-setting decisions by a range of stakeholders, including Regulators, HTA Agencies, Payers, academics and the pharmaceutical industry(2). Identifying a particular condition or disease area as an UMN is intended to signal its health policy significance, stimulate research activities and intensify the development of innovative treatments, diagnoses or health technologies in these areas. List UMN for 2019. include: amyotrophic lateral sclerosis, recurrent glioblastoma, pancreatic cancer. UMN should help to shape policy and action from early phase research, through clinical development to pricing and reimbursement to how a new medicine is used in practice. Access to innovative therapies, including novel, essential innovative medicines, varies widely, with significant differences in per capital use across countries and continents globally. Still, there are UMN for psoriasis, multiple sclerosis, cancers that related to diagnostics and treatment. There is a crucial need for novel antibiotics to stem the tide of antimicrobial resistance, particularly against difficult to treat gram-negative pathogens like Acinetobacter baumannii(2). From the patients’ perspective, innovation is also needed in promoting and/or preserving quality of life; these are also key endpoints. EU pharmaceuticals framework better in order to stimulate innovation in areas of UMN (neurodegenerative, rare diseases and pediatric cancers) (3).